Modest association between peak exercise blood pressure and ambulatory hypertension in endurance athletes. (11th May 2022) - Janssens, K; Mitchell, A; Foulkes, S; Head, G; Saner, N; Howden, E; Claessen, G; La Gerche, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: An exaggerated blood pressure (BP) response to exercise may be an early indicator of hypertension. However, it is common in endurance athletes and the association between systolic blood pressure (SBP) during exercise and hypertension is not well established in this group. Purpose: To establish whether there is an association between exercise-induced hypertension (EIH) and clinical hypertension in endurance athletes. Methods: 250 current and former endurance athletes (16-80 years, 75% male) performed a maximal exercise test on a cycle ergometer with BP measured every 2 min. Athletes were diagnosed with EIH based on international guidelines (SBP ≥210mmHg males, ≥190mmHg females). The relationship between SBP and workload was determined by linear regression analysis. Office hypertension was identified from either supine SBP ≥140mmHg or diastolic BP ≥90mmHg, or if treated for hypertension. Gold-standard 24-hour ambulatory blood pressure monitoring (ABPM) was performed in a subset of 42 athletes with EIH and 9 athletes with a normotensive response to exercise (NRE). Results: On average, peak exercise SBP values were universally high (221±26mmHg in males and 199±21mmHg in females). 71% of athletes (70% of males and 74% of females) met criteria for EIH of which 12% had a peak SBP≥250mmHg. EIH and NRE groups were of similar age, sex, body mass index (BMI) and fitness (Figure 1). The strongest determinant of peak exercise SBP was exercise workload (R=0.78, P<0.001), which remained significant after adjusting for age, sex, BMI and antihypertensive medication (p<0.001) In the full cohort, resting SBP was higher in the EIH group (EIH: 128±13mmHg vs NRE: 122±15mmHg, P=0.006 – Figure 1), however there was a similar prevalence of office hypertension between the EIH (19%) and NRE (15%) groups (P=0.59). This prevalence remained similar (EIH: 13% vs NRE: 10%, P=0.49) after excluding those being treated for hypertension (n=15). In the subset of athletes who underwent 24h ABPM (n=51), there were no diagnoses of clinical hypertension in NRE (n=9, Figure 1). Of the 42 athletes with EIH, a majority (n=32, 76%) were normotensive on ABPM. In the 10 athletes with EIH and hypertension on ABPM, the majority were classified with Grade 1 hypertension (n=5) or daytime hypertension (n=3). Interestingly only two of these athletes would have been identified with office BP measures (see Figure 2). Conclusion: EIH is common in endurance athletes and is strongly associated with peak exercise workloads suggesting this may be a reflection of superior cardiovascular fitness. In a small proportion of athletes, EIH may be associated with mild hypertension.